Influence of tillage methods and fertilizer application on chemical properties of worm castings in a tropical soil - Lal, R.; De Vleeschauwer, D. (1982)
The effects of four rates of N (0, 40, 80 and 120 kg/ha) and three rates of P (0, 13 and 26 kg/ha) on chemical characteristics of soils and earthworm casts for no-tillage and conventionally disc plowed systems were investigated for a tropical Alfisol. Worm casts contained 2.3 to 1.5 times more organic matter, 1.8 to 1.2 times more nitrogen, 1.6 to 1.3 times more Bray-P, 3.2 to 2.1 times more exchangeable Ca2+, 3.8 to 2.5 times more exchangeable Mg2+, 3.1 to 2.2 times more exchangeable K+, and 1.4 to 1.2 times more exchangeable Na+ than the top 10 cm of the soil. The ECEC of worm casts was 3.1 to 2.1 times higher than in the surface soil. The nutrient status of both casts and soil in no-tillage plots was generally superior to that in conventionally plowed treatments. Different rates of N and P application had a significant positive effect on the nutrient status of worm casts. The results are discussed in terms of the role of earthworms in soil productivity.